Factors contributing to financial stability of urban and rural families - Abdul Rahim @ Abdul Wahab, Husniyah; Abdul Samad, M. Fazilah (Universiti Putra Malaysia Press, 2011)
Personality and behavioural aspects may shape the perception on the financial stability of families. Depending on their residential areas, factors contributing to their financial stability might differ. This study attempted to determine factors that have impacts on the financial stability of urban and rural families in Malaysia. Micro-data were obtained through questionnaire form and self-administered by the family financial manager. A ratio of 60 to 40 for the urban and rural areas was used in the quota sampling resulting in responses from 800 family financial managers in Peninsular Malaysia. Meanwhile, the results of binary logistic regression on the separate samples of urban and rural residences revealed significant factors. Financial risk tolerance, future time orientation, self-worth, household income, and cash-flow activities were significantly predictive of perceived financial stability. For urban families, financial risk tolerance, future time orientation and self-worth were less likely to predict financial stability. Household income was positively predicting financial stability of rural families. Budgeting aspect of cash-flow positively influenced financial stability of urban families and record-keeping was positively significant in predicting the financial stability of rural families. Thus, urban and rural families differ in terms of the factors which predict families’ financial stability. Being informed about the factors contributing to financial well-being for the urban and rural families was found to result in better achieving the goals of financial education programme.